2014
DOI: 10.1002/2013jc009327
|View full text |Cite
|
Sign up to set email alerts
|

Decadal sea‐level variability along the coast of Japan in response to ocean circulation changes

Abstract: [1] Decadal sea-level variability along the coast of Japan and its relation to large-scale ocean circulation changes from 1993 to 2010 was investigated using tide-gauge and satellite-derived sea-level data. A singular value decomposition (SVD) analysis is performed between coastal sea levels of Japan and sea levels in the western North Pacific. The first SVD mode reveals that the northward shifts of the Kuroshio Extension (KE) jet and the Kuroshio southeast of Japan accompany the coastal sea-level rise in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 61 publications
(110 reference statements)
9
34
0
Order By: Relevance
“…As for the case of the Gulf Stream, interannual to decadal fluctuations of the KuE can have large impacts on coastal sea level variability. Sasaki et al (2014) have researched sea level variability along the coasts of Japan, primarily on decadal timescales. The first empirical orthogonal function (EOF) mode of sea level variability in the KuE region had previously been shown to describe well the meridional displacements of the KuE on decadal timescales (e.g., Taguchi et al 2007).…”
Section: (A) (B)mentioning
confidence: 99%
See 3 more Smart Citations
“…As for the case of the Gulf Stream, interannual to decadal fluctuations of the KuE can have large impacts on coastal sea level variability. Sasaki et al (2014) have researched sea level variability along the coasts of Japan, primarily on decadal timescales. The first empirical orthogonal function (EOF) mode of sea level variability in the KuE region had previously been shown to describe well the meridional displacements of the KuE on decadal timescales (e.g., Taguchi et al 2007).…”
Section: (A) (B)mentioning
confidence: 99%
“…The first empirical orthogonal function (EOF) mode of sea level variability in the KuE region had previously been shown to describe well the meridional displacements of the KuE on decadal timescales (e.g., Taguchi et al 2007). Sasaki et al (2014) found that northward shifts of the KuE jet and the Kuroshio Current southeast of Japan are accompanied by higher sea levels at the coast. The decadal variability of the KuE latitude is mainly induced by westward-propagating, wind-forced Rossby waves from the eastern North Pacific (Qiu and Chen 2005;Yasuda and Sakurai 2006).…”
Section: (A) (B)mentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the regional sea level changes in the extratropical North Pacific, the lowfrequency changes in the surface wind stress field have also been considered a main driver in determining the regional sea level trends and variability in the western subarctic gyre, the Alaska gyre, the Kuroshio Extension, and off the North America continent (e.g., Qiu 2002;Cummins and Lagerloef 2004;Qiu and Chen 2005;Yasuda and Sakurai 2006;Bromirski et al 2011;Sasaki et al 2014). It is worth emphasizing that away from the coastal orography, the surface wind stress field has generally large spatial scales.…”
Section: Introductionmentioning
confidence: 99%